pass-through of exchange rate changes to the prices of Australian exports of dairy and livestock products - Swift, R (The Australian journal of agricultural and resource economics, 2004)
Agricultural exports are usually assumed to operate in perfectly competitive international markets, but many are subject to non‐tariff barriers to trade that can affect the degree of pass‐through of exchange rate changes to foreign currency prices. The present study uses multivariate cointegration techniques to examine the effects of exchange rate changes on the prices of Australian exports of milk products, cheese, beef, sheepmeat, and hides and skins. The results indicate that Australian dairy exports operate in competitive markets in which pass‐through is complete, but there is no stable long‐run relationship between exchange rates and prices for any of the other livestock products.